The significance of ultrasonographic carpal tunnel outlet measurements in the diagnosis of carpal tunnel syndrome - Csillik, Anita; Bereczki, Dániel; Bora, László; Arányi, Zsuzsanna (Clinical neurophysiology, 2016)
•Median nerve enlargement in CTS is significantly greater at the tunnel outlet than at the inlet.•It is postulated that pressure progressively increases from proximal to distal within the tunnel.•The addition of outlet measurements increases diagnostic sensitivity and accuracy of CTS. A retrospective study to investigate the utility of ultrasonographic carpal tunnel outlet measurements in the diagnosis of carpal tunnel syndrome (CTS). 118 hands of 87 patients with electrophysiologically confirmed CTS and 44 control hands of 23 subjects were assessed. Cross-sectional areas (CSA) of the median nerve were measured at the tunnel inlet, outlet, and forearm. Longitudinal diameters (LAPD) were measured at the inlet, proximal tunnel, distal tunnel, and outlet. CSA at the outlet (median: 18mm2) and its palm-to-forearm-ratio (median: 2.7) were significantly larger than CSA at the inlet (median: 15mm2) and its wrist-to-forearm-ratio (median: 2.2) (p<0.001). 27% of the hands showed enlargement only at the outlet versus 13% only at the inlet. LAPD jump was significantly greater, suggesting relief of higher pressure, at the outlet/distal tunnel versus inlet/proximal tunnel (p<0.001). Median nerve enlargement in CTS is greater at the tunnel outlet than at the inlet. We postulate that this is explained by the progressive increase of pressure within the tunnel from proximal to distal. The addition of CSA outlet measurements to inlet measurements increased CTS ultrasonographic diagnostic sensitivity and accuracy by 15% and 10%, respectively.